A place in the sun [videorecording (DVD)] - Clift, Montgomery; Taylor, Elizabeth, 1932-2011; Winters, Shelley; Stevens, George, 1904-1975; Dreiser, Theodore, 1871-1945 (Paramount DVD collection, 2001)
George Stevens' stunning adaptation of Theodore Dreiser's An American tragedy garnered six Academy Awards and guaranteed immortality for screen lovers Montgomery Clift and Elizabeth Taylor. Clift is a poor young man determined to win a place in respectable society and the heart of beautiful socialite Elizabeth Taylor. Shelley Winters plays the factory girl whose dark secret threatens Clift's professional and romantic prospects. Consumed with fear and desire, Clift is ultimately driven to a desperate act of passion that unravels his world forever.